2010
DOI: 10.1590/s1516-35982010000500030
|View full text |Cite
|
Sign up to set email alerts
|

Correlações entre medidas determinadas in vivo por ultrassom e na carcaça de ovelhas de descarte

Abstract: RESUMO -Objetivou-se estudar as medidas de espessura de gordura subcutânea, área de olho-de-lombo, comprimento e profundidade máxima do músculo longissimus dorsi entre a 13 a costela e 1 a vértebra lombar determinadas por ultrassom e na carcaça de ovelhas de descarte abatidas em diferentes estágios fisiológicos, além dos coeficientes de correlação e determinação das medidas avaliadas. Utilizaram-se 21 ovelhas da raça Santa Inês, distribuídas nos seguintes grupos: OL = ovelhas que permaneceram por 60 dias em la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
3
5
0
7
Order By: Relevance
“…Besides, STF is an attribute that has an important role in meat tenderness for acting as an insulator, thus preventing the rapid carcass cooling, which produces shortening of sarcomeres and increases meat toughness. Pinheiro et al (2010) found values for Longissimus muscle measure A from 5.21 to 5.72 cm in sheep slaughtered at six years of age. These results are similar to the value listed in Table 6 (5.22 cm).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Besides, STF is an attribute that has an important role in meat tenderness for acting as an insulator, thus preventing the rapid carcass cooling, which produces shortening of sarcomeres and increases meat toughness. Pinheiro et al (2010) found values for Longissimus muscle measure A from 5.21 to 5.72 cm in sheep slaughtered at six years of age. These results are similar to the value listed in Table 6 (5.22 cm).…”
Section: Resultsmentioning
confidence: 84%
“…In studies on alternative feed, carcass composition is a very important point to be considered, since it is associated with the carcass yield, meat quality and hence the economic return of the activity; allowing comparisons between breeds, weight and slaughter weight, feeding system, and the correlations with other measures or carcass tissue components (Pinheiro, Jorge, & Yokoo, 2010). Souza, Goes, Silva, Yoshihara, and Prado (2015) evaluated animal performance and carcass characteristics of culling cows fed diets containing crambe crushed replacing soybean meal at 0; 50; 100 and 150 g kg -1 DM in concentrate supplements and observed no effect on the performance and the characteristics of animal carcasses finished on pasture.…”
mentioning
confidence: 99%
“…However, when using this variable one must take into account the factors that might lead to underor overestimates. Factors such as poorly performed skinning, excessive fat removal, altered position of tissues in the carcass, and incorrect cutting of the measured section may alter the accuracy and precision of models (PINHEIRO et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Após jejum de 16 horas de dieta sólida, os animais foram insensibilizados por eletro-narcose, pendurados de cabeça para baixo e cortadas as veias jugulares e artérias carótidas, objetivando a sangria. Após resfriamento da carcaça por 24 horas, foram efetuadas mensurações para cálculo da área de olho de lombo entre a 13 a costela e 1 a vértebra lombar (PINHEIRO et al, 2010). Coletouse uma amostra do músculo Longissimus lumborum, na qual se retirou toda gordura subcutânea, e foram analisados os teores de extrato etéreo, colesterol e ácidos graxos intramusculares.…”
Section: Methodsunclassified